Improvement design of existing threshing machine at Kilang Sawit Risda, Ulu Keratong - Gelau, Daryl; Ting, Joseph Zhi Ho; Chen, Chit Wee; Mohd Rafli, Izzat Emeer; Yahaya, Mohamad Amirul Ashraf; Ramlan, Ikhsan Mustain; Tajurahim, Nurul Ainina Nadhirah; Mahmood, Salwa; Ngadiman, Nor Hasrul Akhmal (Penerbit UTHM, 2020)
Palm oil is very important in the agricultural and economic sectors in Malaysia. It’s origin is in the tropical rain forest region of West Africa, which the main belt runs through the southern latitudes of Cameron, Cote D’ ivoire, Ghana, Liberia, Nigeria, Sierria Leone, Togo and into the equatorial region of Angola and the Congo (FAO,2004). The crude palm oil have a very wide range of application which is about 80% of the crude palm oil (CPO) produced can be converted into food products while the others can be used as non-food applications. The by-products or wasted product of palm oil fruit processing such as empty bunches and fibers can be processed as raw materials for potash fertilizer, pulp and paper manufacturing. The shell fragments can be used as renewable energy as fuels and also for decoration of living apartments.